KERAPATAN DAN KEANEKARAGAMAN VEGETASI BERDASARKAN TUTUPAN LAHAN PADA KELOMPOK HUTAN LINDUNG GUNUNG SIRIMAU PROVINSI MALUKU - Parera, Evelin; Purwanto, Ris Hadi; Permadi, Dwiko Budi; Sumardi, Sumardi (Universitas Pattimura, 2023)
Protected forests are very important to support human life and the environment. One way to determine the condition of protected forests is through land cover. The aim of the research is to determine the condition of the vegetation on the land cover. The research method follows the circular plot method inventory procedure. The data analyzed includes density, the Important Value Index to test the density and level of dominance of vegetation types in an area and the Shannon Wiener Index to test the level of diversity of vegetation types. The highest density value in Primary Dry Land Forest is 15.17% and the Importance Value Index is 69.76%. The density value in secondary dry land forest is 18.37% and the importance value index is 80.02%. The bush density was 25.37% and the important value index was 95.03%. Species diversity in all land cover is included in the medium category with respective values ​​in primary dry land forests of 2.72; secondary dry land forest 2.53 and shrubs 2.07. These three land covers are included in the medium category, which means moderate diversity, sufficient productivity, fairly balanced ecosystem conditions, and moderate ecological pressure.